Supply Chain Fortitude in the Manufacturing Sector: Navigating Global Logistical Disruptions and Shifts in Industrial Confidence - Obyn Imhart Pumpente; Wursan (CV. HEI PUBLISHING INDONESIA, 2026)
Global manufacturing systems face increasing disruptions from geopolitical tensions, pandemic aftershocks, and transportation bottlenecks, threatening supply chain stability and industrial confidence. This study examines supply chain fortitude as an integrative capability encompassing endurance, flexibility, and anticipatory governance. A mixed-method approach was applied, combining cross-regional survey data, structural equation modeling (SEM), and in-depth interviews. The findings reveal that redundancy capacity and digital readiness significantly enhance supply chain fortitude, while disruption frequency negatively affects industrial confidence and decision agility. However, excessive digital investment shows diminishing returns without supplier diversification and organizational alignment. The study highlights that technological integration alone is insufficient, emphasizing the importance of structural and behavioral support mechanisms. Overall, supply chain fortitude is identified as a multidimensional construct integrating technological capability, structural redundancy, and psychological assurance to sustain strategic decision-making under persistent global uncertainty.